2019
DOI: 10.4102/sajr.v23i1.1677
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of basal skull fracture in head injury patients in an academic hospital

Abstract: BackgroundBasal skull fractures (BSFs) have been reported to be a major cause of morbidity and mortality in the literature, particularly in young male patients. However, there are limited data available on the aetiology, prevalence and patterns of such observed in South Africa.ObjectivesTo evaluate the prevalence and pattern of BSF in head injury patients referred to Dr George Mukhari Academic Hospital, Gauteng, South Africa.MethodsPatients of all ages with head injuries were considered for the study, and thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…The pneumatization of temporal bone serves as a prognostic factor in middle ear surgery and could be considered once related surgeries are planned [ 7 – 9 ]. Temporal bone pneumatization has also been reported to give a protective function, acting as a shock absorber in patients with lateral skull-based fracture and traumatic brain injury [ 10 , 11 ], which have had a devastating impact on many individuals, approximately 69 million individuals worldwide and affect a significant number of people in South Africa [ 12 , 13 ]. However, minimal pneumatization of the temporal bone is a characteristic of otitis media [ 14 , 15 ], which is one of the global burdens of disease [ 16 – 20 ], and significantly high in South Africa among younger children and older children with prevalence of 31.4% and 16.7% respectively [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pneumatization of temporal bone serves as a prognostic factor in middle ear surgery and could be considered once related surgeries are planned [ 7 – 9 ]. Temporal bone pneumatization has also been reported to give a protective function, acting as a shock absorber in patients with lateral skull-based fracture and traumatic brain injury [ 10 , 11 ], which have had a devastating impact on many individuals, approximately 69 million individuals worldwide and affect a significant number of people in South Africa [ 12 , 13 ]. However, minimal pneumatization of the temporal bone is a characteristic of otitis media [ 14 , 15 ], which is one of the global burdens of disease [ 16 – 20 ], and significantly high in South Africa among younger children and older children with prevalence of 31.4% and 16.7% respectively [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was also reported in the literature that cerebral contusion was commonly observed in patients with TBI (40.8%) in 2013. 11 In this study, the mean of GCS in the patients with alcohol intoxication was lower than in the patients without alcohol intoxication. A previous study conducted on 108,929 accidents involving alcohol showed that alcohol intoxication did not significantly reduce GCS in patients with TBI at a young age.…”
Section: Discussionmentioning
confidence: 43%
“…This differs from a study conducted by Makolene et al, where it was found that the cranii base fracture of the middle fossa was the most common cranii base compartment followed by the cranii base fracture of the anterior fossa, with base fractures of the posterior cranii recording the least number of fractures. 21 This can be explained by referring to a previous study by Pandhika, where based on the cause, 92% of the head trauma was caused by traffic accidents. 20 Furthermore, the location of the impact in cases of head injury tended to be from the side or the front.…”
Section: Discussionmentioning
confidence: 99%